Implementasi Sistem Informasi Geografis untuk Pemetaan Lokasi Rawan Kecelakaan (Studi Kasus: Kecamatan Jekan Raya Kota Palangka Raya) - Jannatur Rahmah; Murniati; Desi Riani (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Palangka Raya City is a developed urban area with significant traffic flow, especially on primary arterial roads connecting provinces and districts. This condition leads to a high potential for traffic accidents. Jekan Raya District, as one of the districts in Palangka Raya, had a population of 140,173 people in 2019, so the accident risk level in this area is quite high. Population density causes competition for space and limited access to road infrastructure, which exacerbates traffic problems and increases the risk of accidents. Geographic Information Systems (GIS) can be used as an alternative to analyze and generate maps of areas and accident-prone areas in Jekan Raya District. Based on calculations of accident and fatality rates on Jalan Tjilik Riwut, the average accident rate from 2018-2022 reached 7.22% with a fatality rate of 1.19% per 100 million vehicle trips. Several roads classified as black sites include Jalan Tjilik Riwut (181 incidents), Jalan G. Obos (58), Jalan RTA Milono (38), and others. This data serves as an important reference in managing locations prone to traffic accidents.